Valence and spin states of iron are invisible in Earth’s lower mantle - Jiachao Liu; Susannah M. Dorfman; Feng Zhu; Jie Li; Yonggang Wang; Dongzhou Zhang; Yuming Xiao; Wenli Bi; E. Ercan Alp (Nature Communications, 2018)
Bridgmanite is the most abundant mineral in the lower mantle and therefore is crucial to interpreting geophysical observations and models. Here, the authors show that ferric-iron-only bridgmanite Fe3+ undergoes a spin transition at 43–53 GPa at 300 K and therefore has implications for mantle structure and dynamics.